Find the sum of all possible y values for which y 3 = x 3 + 8 x 2 − 6 x + 8 where x and y are non-negative integers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think this is an old RMO/INMO question. Plus, You can also prove that y 3 > ( x + 1 ) 2 , leaving only the y = x + 2 case
Can one of you explain how you're proving these inequalities to be true? Just curious.
Log in to reply
We are told y 3 = x 3 + 8 x 2 − 6 x + 8
We want to prove that ( x + 3 ) 3 ≥ y 3 = x 3 + 8 x 2 − 6 x + 8
Expanding and rearranging we get:
x 2 + 3 3 x + 1 9 ≥ 0 Since all coeficients are positive and x must be a positive number that inequality is true.
Just substitute the value of y 3 in the inequality and taking all the terms to the LHS will give you x > 0
Another solution:
y^3 = x^3 + 8x^2 - 6x + 8 = (x^3 + 6x^2 + 12x + 8) + (2x^2 - 18x) = (x + 2)^3 + 2x(x - 9).
Since the right-hand side has degree 3 with (x + 2)^3, the trivial solution here is to make the remaining terms (2x^2 - 18x) zero which is when x = 0 and x = 9 giving y = 2 and y = 11 respectively. We prove that there are no more solutions aside from these by using the gaps between perfect cubes.
Since (x + 1)^3 - x^3 = 3x^2 + 3x + 1, we compare 3x^2 + 3x + 1 > 2x^2 - 18x gives the inequality x^2 + 21x + 1 > 0 which is true for all positive integers. which implies no more solutions aside from y = 2 and y = 11.
If we put y = x + k (where k is a positive or a negative integer), we obtain a quadratic
x^2(8 - 3k) - x(6 + 3k^2) + (8 - k^3) = 0 with a discriminant
D = -3k^4 + 32k^3 + 36k^2 + 96k - 220.
In order to make D positive, we choose 1 < k > 12 and for k = 2 we have D = 18^2, which yields two solutions for y: 2 and 11. My approach to this problem wasn't nearly as straightforward as in the other two solutions, because it involved lots of calculation, but with this type of problems the first instinct is almost always to check the quadratic discriminant.
Problem Loading...
Note Loading...
Set Loading...
It can be proved easily that ( x + 3 ) 3 > y 3 > x 3 Since both x and y are integers we have either y = x + 1 or y = x + 2 . Putting this into the equation we obtain x = 0 and x = 9 as solutions(Both occur when y = x + 2 ).
Putting x = 0 we get y = 2 .
Putting x = 9 we get y = 1 1 .
So the sum of all possible y-values = 2 + 1 1 = 1 3